Analizyng The Lingual Elements of Sampoerna Hijau Advertisement Published on Youtube - Sara Oktaviyanti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
The research aims to find any lingual elements and meanings used by advertisers in â€œSampoerna Hijauâ€ Cigarette advertisements on Youtube. There are 5 editions of advertisements that are analized, â€œEdisi Dateng Kondanganâ€, â€œEdisi Selfie di Kondanganâ€, â€œEdisi Minum Es Kacang Ijoâ€, â€œEdisi Punyaku Lebih Nikmatâ€ and the last is â€œEdisi Hijau Panasâ€. Seven Types of Meaning theory by Leech is used on this research. This study is design in a qualitative research. Researcher collected the data using observation methods. Then in the analysis of research data using Agih method with the basic technique that is Bagi Unsur Langsung or BUL techniques. The BUL method and technique are used by researcher to analyze the signs and forms found in Sampoerna Hijau cigarette advertisements so that they can easily classify these lingual signs and forms. The researcher found that the lingual form in the five editions of Sampoerna Hijau Cigarette Advertisements, namely: 10 interrogative sentences, 13 imperative sentences, 13 declarative sentences, 14 exclamation sentences, 2 nouns and 1 adjective. The meanings found in each lingual form are 5 meanings, with the following description: sentences that contain reflections as many as 12 sentences, sentences containing affective meanings of 22 sentences, sentences containing conceptual meanings of 15 sentences, sentences that contains a colloquial meaning of 2 sentences and the last sentence that contains connotative meaning of 1 sentence.